The Use of Design Thinking Methods in the Development of Telkomedika Mobile Applications for Patients with Conscientiousness Personality Types - Hilzahra Putrie Dienya; Ilham Perdana; Hilda Nuraliza (Jurnal Indonesia Sosial Teknologi, 2024)
This research aims to improve the quality of Telkomedika Telkom University Clinic services by developing a mobile application that is tailored to the personality type of patients with conscientiousness. This Mobile Application is designed to fulfill the patient's need for service information through the service information feature and streamline the queuing process through the online reservation feature. Through the use of the DISC personality type approach, this study focuses on the preferences and characteristics of patients to increase satisfaction. Users or patients with this conscientious personality type tend to be meticulous, systematic, and structured. Therefore, a structured interface design and also an easy-to-understand task flow will help users in using the application efficiently. The results of the study show the importance of understanding user preferences in designing applications. Usability Testing on the Telmed 2.0 application prototype resulted in a Single Ease Question (SEQ) score of 6.88, indicating ease of use. In addition, User Acceptance Testing showed that all features worked well, with a score of 91.5 on the System Usability Scale (SUS), indicating an excellent level of ease of use of the application.